Human resources for health : overcoming the crisis (Global Equity Initiative : Distributed by Harvard University Press, 2004)
In this analysis of the global workforce, the Joint Learning Initiative, a consortium of over 100 health leaders, proposes that mobilization and strengthening of human resources for health, neglected yet critical, is central to combating health crises in some of the world's poorest countries and for building sustainable health systems everywhere.